2020
DOI: 10.4193/rhin20.196
|View full text |Cite
|
Sign up to set email alerts
|

Individual importance of olfaction decreases with duration of smell loss

Abstract: Background: The personal importance of a lost neurologic-motor or sensory-function in several conditions has been shown to decrease as the afflicted patient becomes accustomed to not having that function. It is unknown how the importance of olfaction changes with duration of olfactory dysfunction (OD). The aim of this study was to evaluate the association between duration of smell loss and individual significance of olfaction, and whether this relationship would be modulated by other factors, such as etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Moreover, we previously found a negative correlation between duration of smell loss and the individual significance of olfaction, suggesting the possibility of internal frameshifts over time leading to less overall importance of olfaction to patients with OD. 25 Interestingly, orthonasal olfactory function (as measured with the Sniffin’ Sticks test) showed significant associations with the QOD-positive statement score in only our univariate regression model, not in multivariable analysis. However, this finding was not unexpected, since a previous study also reported no relevant correlation between measured olfactory function and the QOD-positive statement score of patients with OD.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, we previously found a negative correlation between duration of smell loss and the individual significance of olfaction, suggesting the possibility of internal frameshifts over time leading to less overall importance of olfaction to patients with OD. 25 Interestingly, orthonasal olfactory function (as measured with the Sniffin’ Sticks test) showed significant associations with the QOD-positive statement score in only our univariate regression model, not in multivariable analysis. However, this finding was not unexpected, since a previous study also reported no relevant correlation between measured olfactory function and the QOD-positive statement score of patients with OD.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies suggested that duration of smell loss and patient’s age might be correlated with greater coping with OD. 25 We therefore sought to determine whether these variables also show relevant correlations and associations in our cohort of patients with OD ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients that were included in this analysis received OT for up to 9 months, which is longer than the usually recommended duration of treatment. Since OT is usually recommended for at least six months (twice on a daily base), informing patients (and thus increasing the likelihood of treatment adherence 28,29 ) remains a cornerstone during counseling.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] In contrast, olfactory dysfunction has previously been found to not correlate with patientreported CRS control in comparison to other nasal symptoms. 38,39 Moreover, whereas olfactory dysfunction is associated with decreased quality of life, its relative importance to the patient appears to diminish over time 10 and is replaced by a focus on a dominant symptom such as nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, chronic sinonasal inflammation due to CRS may also contribute to irreversible damage of the olfactory sensory nerves leading to the loss of smell that persists regardless of the control of sinonasal mucosal inflammation. Moreover, recent studies have indicated that the importance patients place on smell loss decreases with time 10 and is more weakly correlated with a decrease in quality of life when compared to nasal obstruction and rhinorrhea in CRS patients. 11 Based on these findings, we sought to determine the extent to which smell loss is a determinant of patient-reported CRS control, independent of symptoms of nasal obstruction and rhinorrhea.…”
Section: Introductionmentioning
confidence: 99%